Plant physiology - Taiz, Lincoln (Sinauer Associates, 2006)
This fourth edition provides the basics for introductory courses on plant physiology without sacrificing the more challenging material sought by upper division and graduate level students. Many new or revised figures and photographs, study questions and a glossary of key terms have been added.